Способ брикетирования коксовой пыли - Папин А. В.; Солодов В. С.; Косинцев В. И. Виктор Иванович; Сечин А. И. Александр Иванович; Черкасова Т. Г.; Игнатова А. Ю.; Неведров А. В.; Макаревич Е. А.
опубл. 27.11.12.